IPTEKS STANDAR AKUNTANSI PEMERINTAH PADA ASET TETAP BPKP PERWAKILAN PROVINSI SULAWESI UTARA - Selah, Ridel Fendri; Ilat, Ventje (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
The North Sulawesi BPKP financial report is a report made to account for the performance results as a government agency.Â  Government Accounting Standards are principles and rules that are made as a basis for making financial statements for the government. Fixed assets are one component of assets reported in financial statements that are used for more than one year. For this reason, reporting must be correct and accordance with applicable accounting standards. The purpose of this study is to analyze the suitability between Government Accounting Standards and reporting of Fixed Assets in the North Sulawesi BPKP. The method used is the analysis of the fixed asset report of North Sulawesi BPKP with Government Accounting Standards.Â  The results of his research in Asset reporting are in accordance with the applicable Standards, only the difference in completeness is that there is a fixed asset account that has not been included in the 2017 report. In the future only enter an account that does not exist for the completeness of the fixed assets account if there is already an asset.Keywords : Government Accounting Standard, Financial Report, Fixed Asset